Porous silicon-carbon composite negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

By using PECVD technology to deposit silicon and lithium into porous carbon in one-step method at low temperatures and perform carbon coating, the problem of silicon carbon anode materials in the prior art is difficult to take into account high capacity, high first-time efficiency and high cycle performance, and a high efficient and low-cost preparation process is achieved.

CN119725429APending Publication Date: 2025-03-28NINGBO FULI BATTERY MATERIAL TECH CO LTD +1

Patent Information

Application Number
CN202411698042.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing silicon-carbon anode materials are difficult to take into account both high capacity, high first-time efficiency and high cycle performance, and the preparation process is complex, energy consumption is high, and the cost is high.

Method used

PECVD technology was used to deposit silicon and lithium into porous carbon in one-step at a low temperature of 300-550°C, and carbon coating was carried out to prepare porous silicon-carbon composite anode material.

Benefits of technology

While achieving high capacity, the first-time efficiency and cycling performance are improved, the preparation energy consumption is reduced, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725429A_ABST
    Figure CN119725429A_ABST
Patent Text Reader

Abstract

The invention provides a porous silicon-carbon composite negative electrode material and a preparation method thereof, a negative electrode plate and a lithium ion battery. The invention relates to a preparation method of a porous silicon-carbon composite negative electrode material, which comprises the following steps: depositing silicon and lithium: uniformly mixing a lithium salt and porous carbon, putting the mixture into PECVD (Plasma Enhanced Chemical Vapor Deposition) equipment, vacuumizing the PECVD equipment, heating to the deposition temperature of 300-550 DEG C, introducing inert gas and silane gas into the PECVD equipment, and depositing silicon and lithium on the porous carbon under the condition that the power of a radio frequency power supply is 400-600W, a negative electrode material precursor is obtained; wherein the specific surface area of the porous carbon is 1000-2000 m < 2 > / g; and carbon coating: carrying out carbon coating on the negative electrode material precursor to obtain the porous silicon-carbon composite negative electrode material. According to the preparation method, silicon and lithium can be more uniformly deposited into porous carbon through a low-temperature deposition one-step method, and carbon coating is more uniform and compact, so that the obtained porous silicon-carbon composite negative electrode material has higher first efficiency and better cycle performance while having high capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a porous silicon-carbon composite negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium-ion battery. Background Art

[0002] As an energy storage device with outstanding performance, lithium-ion batteries are widely used in new energy storage power supply systems, power tools, new energy vehicles, military equipment, aerospace and other fields. People have put forward higher requirements for the energy density, rate performance, cycle performance, high and low temperature performance, etc. of the new generation of lithium-ion batteries. In view of the development requirements of energy density, improving the specific capacity of electrode materials is the most direct and effective method.

[0003] The theoretical gram capacity of silicon-based negative electrode materials can reach 4200mAh / g, and it also has a low lithium insertion and extraction potential, making it a battery material with great application potential. However, the huge volume expansion not only shortens the battery cycle life, but also limits the application of this material in high-end electronic devices. At the same time, silicon-based negative electrode materials form a large amount of SEI film during the first charge and discharge process, which easily consumes active lithium ions and causes a decrease in the first coulomb efficiency. Therefore, the preparation of a silicon-based negative electrode material with high first efficiency, long cycle performance and low expansion coefficient has become the focus and difficulty of research and development in the battery negative electrode material industry.

[0004] For example, a Chinese patent application (CN117577819A) provides a method of first depositing metallic lithium into porous carbon in a fluidized bed CVD device, and then depositing nano-silicon into the porous carbon, followed by carbon coating to form an amorphous carbon shell; the core includes nano-silicon, nano-silicon lithium alloy and porous carbon material. The silicon-carbon material prepared by this method slows down the expansion of the battery, thereby improving the cycle performance of the battery. However, the disadvantages of this patent application are: First, the deposition of lithium and nano-silicon in a fluidized bed CVD requires a relatively high temperature of 600°C-1800°C, which consumes a lot of energy; Second, the application of the material in lithium batteries does not clearly point out that the problem of low efficiency of silicon-carbon negative electrode materials has been solved.

[0005] In summary, researchers have conducted a lot of attempts to design the structure and components of silicon-carbon negative electrode materials. In terms of electrochemical performance, negative electrode materials cannot achieve high capacity, high initial efficiency and high cycle performance. At the same time, the material preparation process is complex, the production energy consumption is huge, and the production cost is high. Summary of the invention

[0006] The present disclosure provides a porous silicon-carbon composite negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium ion battery, so as to at least solve one of the technical problems existing in the prior art.

[0007] According to a first aspect of the present disclosure, a method for preparing a porous silicon-carbon composite negative electrode material is provided, comprising:

[0008] Deposition of silicon and lithium: After the lithium salt and porous carbon are evenly mixed, they are placed in a PECVD device, the PECVD device is evacuated, the temperature is raised to a deposition temperature of 300-550°C, inert gas and silane gas are introduced into the PECVD device, and a radio frequency power supply power of 400-600W is used to deposit silicon and lithium on the porous carbon to obtain a negative electrode material precursor; wherein the specific surface area of ​​the porous carbon is 1000-2000m 2 / g;

[0009] Carbon coating: The negative electrode material precursor is carbon coated to obtain a porous silicon-carbon composite negative electrode material.

[0010] In one embodiment, the porous silicon-carbon composite negative electrode material includes a core and an outer shell; the core includes porous carbon and silicon and lithium deposited on the porous carbon, the core content is 97-98.2wt%, the outer shell is a carbon coating layer, the carbon coating layer content is 1.8-3.0wt%, wherein the lithium content in the core is 2-7wt%, and the silicon content is 40-50%.

[0011] In one embodiment, the lithium salt is an inorganic lithium salt or an organic lithium salt; the inorganic lithium salt is one or more of lithium amide, lithium hydride, lithium hydroxide, and lithium carbonate; the organic lithium salt is one or more of methyl lithium, lithium acetate, lithium octanoate, lithium tetrahydroborate, lithium stearate, and lithium acetate;

[0012] The average pore size of the porous carbon is 1.0 to 2.0 nm;

[0013] The vacuum degree of the PECVD equipment is 1.0×10 -4 ~1.0×10 -1 Pa;

[0014] The PECVD equipment is heated to 300-550° C. at a heating rate of 2-10° C. / min.

[0015] In one embodiment, during the deposition of silicon and lithium, the flow ratio of the inert gas to the silane gas is 10:60 to 60:60.

[0016] In one embodiment, the inert gas is a mixture of one or more of nitrogen, argon and helium;

[0017] The silane gas is a mixture of one or more of monosilane and disilane;

[0018] When the silicon and lithium are deposited on the porous carbon, the reflected power of the PECVD device is 200-300W.

[0019] In one possible implementation, during the carbon coating, an inert gas and a carbon source gas need to be introduced into the PECVD device; wherein the flow ratio of the inert gas to the carbon source gas is 10:60 to 60:60.

[0020] In one embodiment, the carbon source gas is a mixture of one or more of methane, acetylene, ethylene, and propylene; and the inert gas is a mixture of one or more of nitrogen, argon, and helium.

[0021] According to a second aspect of the present disclosure, a porous silicon-carbon composite negative electrode material is provided, which is obtained by the preparation method described in any one of the above-mentioned embodiments.

[0022] According to a third aspect of the present disclosure, a negative electrode sheet is provided, wherein the negative electrode sheet comprises the porous silicon-carbon composite negative electrode material.

[0023] According to a fourth aspect of the present disclosure, a lithium-ion battery is provided, comprising the negative electrode sheet.

[0024] Compared with the prior art, the advantages of this application are: 1) This application can deposit silicon and lithium into porous carbon more evenly through the one-step "low-temperature deposition" method, and the carbon coating is more uniform and dense, so that the obtained porous silicon-carbon composite negative electrode material has high capacity, better first efficiency and better cycle performance. 2) The deposition temperature of this application is carried out at a lower temperature of 300 to 550°C. Compared with the deposition temperature of 700°C to 1000°C in the current preparation process, the method of this application can greatly reduce energy consumption.

[0025] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:

[0027] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.

[0028] Figure 1 A scanning electron microscope image of the porous silicon-carbon composite negative electrode material of Example 2 of the present disclosure is shown;

[0029] Figure 2 The charge and discharge curves of the porous silicon-carbon composite negative electrode material of Example 2 of the present disclosure are shown. DETAILED DESCRIPTION

[0030] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0031] According to one embodiment of the present disclosure, the present invention provides a method for preparing a porous silicon-carbon composite negative electrode material.

[0032] A method for preparing a porous silicon-carbon composite negative electrode material, comprising:

[0033] Deposition of silicon and lithium: After the lithium salt and porous carbon are evenly mixed, they are placed in a PECVD device, the PECVD device is evacuated, the temperature is raised to a deposition temperature of 300-550°C, inert gas and silane gas are introduced into the PECVD device, and silicon and lithium are deposited on the porous carbon under the condition of a radio frequency power of 400-600W to obtain a negative electrode material precursor; wherein the specific surface area of ​​the porous carbon is 1000-2000m 2 / g;

[0034] Carbon coating: At the same temperature as the deposition temperature, the negative electrode material precursor is carbon coated to obtain a porous silicon-carbon composite negative electrode material.

[0035] The PECVD equipment in this application adopts a plasma enhanced chemical vapor deposition equipment (PECVD). The porous silicon-carbon composite negative electrode material of this application deposits nano-silicon and lithium in porous carbon by plasma enhanced chemical vapor deposition (PECVD) technology, and then carbon-coated to obtain a porous silicon-carbon composite negative electrode material (referred to as "negative electrode material", the same below), which has high first efficiency (i.e., first coulomb efficiency), long cycle life and low expansion coefficient.

[0036] The present application can more evenly deposit silicon and lithium into porous carbon through a one-step "low-temperature deposition" method in a plasma enhanced chemical vapor deposition device, and the carbon coating is more uniform and dense, so that the obtained porous silicon-carbon composite negative electrode material has a high capacity while having better first efficiency and better cycle performance.

[0037] The present application applies a radio frequency (RF) electric field in a plasma enhanced chemical vapor deposition (PECVD) reaction chamber. This electric field can ionize some molecules or atoms in the gas to form plasma. The use of PECVD enhances the chemical reaction, allowing the process to be carried out at a lower temperature (300-550°C). Compared with the deposition temperature of 700°C to 1000°C in the current preparation process, the method of the present application can greatly reduce energy consumption.

[0038] In the preparation of the porous silicon-carbon composite negative electrode material of the present application, a silicon-carbon composite negative electrode material with high initial efficiency, high capacity and low expansion is prepared by a one-step method using plasma enhanced vapor deposition technology (PECVD). This method only requires one step to deposit nano-silicon and nano-lithium into porous carbon. Porous carbon can alleviate the expansion of silicon during the charge and discharge process and improve the initial efficiency and cycle expansion performance of lithium batteries. In addition, the additional deposited lithium is equivalent to adding more lithium sources to the negative electrode material, which can significantly improve the initial efficiency of the negative electrode material.

[0039] Furthermore, the deposition temperature of plasma enhanced vapor deposition technology is only 300-550°C, which significantly reduces the energy consumption in the entire negative electrode material preparation process, and is more conducive to reducing the cost of industrialization of silicon-carbon negative electrode materials.

[0040] For example, the porous silicon-carbon composite negative electrode material obtained by the preparation method of the present application includes a core and an outer shell, the outer shell is a carbon coating layer, and the core includes porous carbon and silicon and lithium mainly deposited in the pores of the porous carbon. Among them, the content of the carbon coating layer is 1.8-3.0wt% (for example, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%), the content of the core is 97-98.2wt%, the content of lithium included in the core is 2-7wt%, the content of silicon is 40-50wt%, and the remainder is porous carbon and other substances loaded in the pores of porous carbon (if any), for example, the other substances can be the remaining components other than lithium when the lithium salt is decomposed and deposited. Of course, for example, when the lithium salt is lithium hydride or methyl lithium, only lithium element is deposited in the pores of the porous carbon when the lithium hydride / methyl lithium is deposited and decomposed.

[0041] Preferably, the lithium salt is an inorganic lithium salt or an organic lithium salt; the inorganic lithium salt is one or more of lithium amide, lithium hydride, lithium hydroxide, and lithium carbonate; the organic lithium salt is one or more of methyl lithium, lithium acetate, lithium octanoate, lithium tetrahydroborate, lithium stearate, and lithium acetate.

[0042] Preferably, the average pore size of the porous carbon is 1.0-2.0 nm; for example, the average pore size is 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2.0 nm. The specific surface area of ​​the porous carbon is 1000 m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g.

[0043] Preferably, the vacuum degree of the PECVD equipment is 1.0×10 -4 ~1.0×10 -1 Pa.

[0044] Preferably, the PECVD device is heated to a deposition temperature of 300-550°C at a heating rate of 2-10°C / min; for example, the deposition temperature is 300°C, 350°C, 400°C, 450°C, 500°C, 550°C. In the present application, the deposition temperature is set at 300-550°C because, when the deposition temperature is less than 300°C, the lithium salt cannot be decomposed and deposited into the porous carbon material. If the deposition temperature is greater than 550°C, it will cause greater energy consumption.

[0045] Preferably, in the deposition of silicon and lithium, the flow ratio of the inert gas to the silane gas is 10:60 to 60:60 sccm, for example, the flow ratio of the inert gas to the silane gas is 10:60, 20:60, 30:60, 40:60, 50:60, 60:60.

[0046] Preferably, the inert gas is a mixture of one or more of nitrogen, argon and helium.

[0047] Preferably, the silane gas is a mixture of one or more of monosilane and disilane.

[0048] Preferably, when silicon and lithium are deposited on the porous carbon, the reflected power of the PECVD equipment is 200-300W.

[0049] In the present application, the RF power is 400W-600W (for example, the RF power is 400W, 450W, 500W, 550W, 600W), the reflected power is 200-300W, and the lithium salt is decomposed and deposited into the porous carbon under high temperature while nano-silicon is deposited on the porous carbon material (because the active sites of the porous carbon are basically in the pores of the porous carbon, and there are few active sites outside the porous carbon, and combined with Figure 1 The SEM image shows that there is no obvious floating silicon and floating lithium on the surface of the final negative electrode material.

[0050] Preferably, during carbon coating, an inert gas and a carbon source gas need to be introduced into the PECVD device, wherein the flow ratio of the inert gas to the carbon source gas is 10:60 to 60:60. For example, the flow ratio of the inert gas to the carbon source gas is 10:60, 20:60, 30:60, 40:60, 50:60, 60:60.

[0051] Preferably, the carbon source gas is a mixture of one or more of methane, acetylene, ethylene, and propylene; and the inert gas is a mixture of one or more of nitrogen, argon, and helium.

[0052] According to the second aspect of the present disclosure, the present application provides a porous silicon-carbon composite negative electrode material, which is obtained by the above-mentioned preparation method.

[0053] According to a third aspect of the present disclosure, the present application provides a negative electrode sheet comprising a porous silicon-carbon composite negative electrode material.

[0054] According to a fourth aspect of the present disclosure, the present application provides a lithium-ion battery comprising a negative electrode sheet.

[0055] The present application is further described in detail below with reference to specific embodiments:

[0056] Embodiment 1:

[0057] A method for preparing a porous silicon-carbon composite negative electrode material: comprising:

[0058] Weigh 20g, average pore size 2nm, specific surface area 1800m 2 / g of porous carbon material and 1.02g of lithium hydride were mixed evenly, and placed on the substrate stage of a plasma chemical vapor deposition device; the device was evacuated to a vacuum degree of 1.0×10 -3Pa; heating the substrate stage at a heating rate of 5°C / min to 450°C; introducing argon and monosilane gases into the plasma chemical vapor deposition equipment, with a flow ratio of argon to monosilane of 60:60sccm; turning on the RF power supply at 500W and a reflected power of 250W to deposit silicon on the porous carbon material for 278min, during which lithium hydride is slowly decomposed and deposited into the porous carbon; after the silicon deposition reaction is completed, introducing argon and acetylene at a flow ratio of 20:60sccm for 13min, and finally obtaining 42.51g of porous silicon-carbon composite negative electrode material.

[0059] Embodiment 2:

[0060] A method for preparing a porous silicon-carbon composite negative electrode material: comprising:

[0061] First weigh 20g, average pore size 2nm, specific surface area 1800m 2 / g of porous carbon material and 2.27g of lithium hydride were mixed evenly and placed on the substrate stage of a plasma chemical vapor deposition device; the device was evacuated to a vacuum degree of 1.0×10 -3 Pa; heating the substrate stage at a heating rate of 5°C / min to 450°C; introducing argon and monosilane gases into the plasma chemical vapor deposition equipment, with a flow ratio of argon to monosilane of 60:60sccm; turning on the RF power supply at 500W and a reflected power of 250W, depositing silicon on the porous carbon material for 283min, while lithium hydride is slowly decomposed and deposited into the porous carbon during the deposition of silicon, and after the silicon deposition reaction is completed, starting to introduce argon and acetylene at a flow ratio of 20:60sccm for 15min, and finally obtaining 44.18g of porous silicon-carbon composite negative electrode material.

[0062] Example 3

[0063] A method for preparing a porous silicon-carbon composite negative electrode material: comprising:

[0064] First weigh 20g, average pore size 2nm, specific surface area 1800m 2 / g of porous carbon material and 9.5g of methyl lithium were mixed evenly, and placed on the substrate stage of a plasma chemical vapor deposition device; the device was evacuated to a vacuum degree of 1.0×10 -3Pa; heating the substrate stage at a heating rate of 5°C / min to 550°C; introducing argon and monosilane gases into the plasma chemical vapor deposition equipment, with a flow ratio of argon to monosilane of 60:60sccm; turning on the RF power supply at 500W and a reflected power of 250W, depositing silicon on the porous carbon material for 260min, while methyl lithium is slowly decomposed and deposited into the porous carbon during the deposition of silicon, and after the silicon deposition reaction is completed, introducing argon and acetylene at a flow ratio of 20:60sccm for 14min, and finally obtaining 43.55g of porous silicon-carbon composite negative electrode material.

[0065] Comparative Example 1 (Compared with Example 1, without adding lithium source)

[0066] A method for preparing a porous silicon-carbon composite negative electrode material: comprising:

[0067] First weigh 20g, average pore size 2nm, specific surface area 1800m 2 / g porous carbon material, placing it on the substrate stage of a plasma chemical vapor deposition device; evacuating the device to a vacuum degree of 1.0×10 -3 Pa; heating the substrate stage with a heating rate of 5°C / min to make the deposition temperature at 450°C; introducing argon and monosilane gases into the plasma chemical vapor deposition equipment, with the flow ratio of argon to monosilane being 60:60sccm; turning on the RF power supply with a power of 500W and a reflected power of 250W, depositing silicon on the porous carbon material with a reaction time of 266min, and starting to introduce argon and acetylene after the silicon deposition reaction is completed, with a flow ratio of 20:60sccm and an introduction time of 13min, to finally obtain 40.95g of porous silicon-carbon composite negative electrode material.

[0068] Comparative Example 2: (Compared with Example 2, no lithium source was added)

[0069] A method for preparing a porous silicon-carbon composite negative electrode material: comprising:

[0070] First weigh 20g, average pore size 2nm, specific surface area 1800m 2 / g porous carbon material, placing it on the substrate stage of a plasma chemical vapor deposition device; evacuating the device to a vacuum degree of 1.0×10 -3Pa; heating the substrate stage with a heating rate of 5°C / min to make the deposition temperature at 450°C; introducing argon and monosilane gases into the plasma chemical vapor deposition equipment, with the flow ratio of argon to monosilane being 60:60sccm; turning on the RF power supply with a power of 550W and a reflected power of 250W, depositing silicon on the porous carbon material with a reaction time of 256min, and starting to introduce argon and acetylene after the silicon deposition reaction is completed, with a flow ratio of 20:60sccm and an introduction time of 13min, to finally obtain 40.02g of porous silicon-carbon composite negative electrode material.

[0071] Comparative Example 3: (Compared with Example 3, no lithium source was added)

[0072] A method for preparing a porous silicon-carbon composite negative electrode material: comprising:

[0073] First weigh 20g, average pore size 2nm, specific surface area 1800m 2 / g porous carbon material, placing it on the substrate stage of a plasma chemical vapor deposition device; evacuating the device to a vacuum degree of 1.0×10 -3 Pa; heating the substrate stage with a heating rate of 5°C / min to make the deposition temperature at 550°C; introducing argon and monosilane gases into the plasma chemical vapor deposition equipment, with the flow ratio of argon to monosilane being 60:60sccm; turning on the RF power supply with a power of 550W and a reflected power of 250W, depositing silicon on the porous carbon material with a reaction time of 227min, and starting to introduce argon and acetylene after the silicon deposition reaction is completed, with a flow ratio of 20:60sccm and an introduction time of 12min, to finally obtain 37.84g of porous silicon-carbon composite negative electrode material.

[0074] Comparative Example 4: (Using CVD)

[0075] A method for preparing a porous silicon-carbon composite negative electrode material: comprising:

[0076] First weigh 20g, average pore size 2nm, specific surface area 1800m 2 / g of porous carbon material and 2.27g of lithium hydride are evenly mixed, and the mixture is put into a chemical vapor deposition device (CVD). Argon is introduced and the temperature is raised to 680°C at a rate of 5°C / min. Then, argon and monosilane gases are introduced into the chemical vapor deposition device, and the flow ratio of argon to silane gas is 60:60sccm. Silicon is deposited on the porous carbon material, and the reaction time is 283min. While silicon is being deposited, lithium hydride is also slowly decomposed and deposited into the porous carbon. After the silicon deposition reaction is completed, the temperature is raised to 850°C at a rate of 5°C / min, and argon and acetylene are introduced at a flow ratio of 20:60sccm for 13min to finally obtain 44.06g of porous silicon-carbon composite negative electrode material.

[0077] Characterization and Testing:

[0078] 1: The porous silicon-carbon composite negative electrode materials prepared in the above embodiments and comparative examples were subjected to ICP test and TG test to obtain the silicon Si deposition content, lithium Li deposition content and carbon coating layer content. The results are listed in Table 1.

[0079] 2: The porous silicon-carbon composite negative electrode material prepared in Example 2 was subjected to a scanning electron microscope (SEM) test. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that there is no obvious floating silicon and floating lithium on the surface of the porous silicon-carbon composite negative electrode material, and there are no obvious pores and defects on the surface of the material after secondary coating.

[0080] 3: The porous silicon-carbon composite negative electrode material prepared in the above embodiments and comparative examples is dispersed in water with a conductive agent and a binder in a certain proportion (porous silicon-carbon composite negative electrode material: polyacrylic acid PAA: carbon nanotube CNT: conductive agent SP = 85:5:0.5:9.5), prepared into a slurry, scraped on a copper foil, and dried, rolled, and cut to obtain a negative electrode sheet.

[0081] Using the negative electrode sheet as the working electrode, the metal lithium sheet as the counter electrode, PP material Celgard 25000 as the separator, 1.0M LiPF6 / EC:DEC:DMC (volume ratio of 1:1:1) as the electrolyte, a simulated battery (shell model is 2016) was assembled in an argon-filled glove box to obtain a button battery.

[0082] The electrochemical performance of the button cell was tested using a Blue Electric 5V / 10mA battery tester, with a charging voltage of 2V, a discharge voltage of 0.005V, a current rate of 0.1C for the first cycle of charge and discharge, and a current rate of 0.2C for the cycle test. The results are listed in Table 1.

[0083] Table 1 Element content analysis results of porous silicon-carbon composite negative electrode materials

[0084]

[0085]

[0086] From Table 1, it can be seen that the first efficiency of the porous silicon-carbon composite negative electrode material prepared in Examples 1-3 is much greater than the first efficiency of Comparative Examples 1-3; the capacity retention rate of the porous silicon-carbon composite negative electrode material of Examples 1-3 after 200 cycles is greater than the cycle capacity retention rate of Comparative Examples 1-3. This shows that the addition of a lithium source and the deposition of the lithium source on porous carbon improve the first efficiency and cycle capacity retention rate of the porous silicon-carbon composite electrode material finally prepared.

[0087] In addition, by comparing the present embodiment 2 and comparative example 4, even if the porous carbon material, lithium salt, and silane material required for preparing the porous silicon-carbon composite negative electrode material are the same, the different deposition equipment and necessary process parameters used will also lead to a large difference in the first efficiency and cycle capacity retention rate of the prepared negative electrode material. Specifically, comparative example 4 uses chemical vapor deposition equipment for vapor deposition, and the deposition temperature is as high as 850°C; while the present embodiment 2 uses plasma chemical vapor deposition equipment, the deposition temperature is at a low temperature of 450°C, and the radio frequency power supply power is 500W; the first efficiency and cycle retention rate of the negative electrode materials prepared by the two are quite different. It can be seen from Table 1 that the first efficiency of the negative electrode material of the present embodiment 2 is greater than the first efficiency of comparative example 4, and the cycle retention rate is also much greater than the cycle retention rate of the negative electrode material of comparative example 4. In addition, it can also be seen from the above Table 1 that the first expansion rate of the porous silicon-carbon composite negative electrode material prepared in the present embodiment 1-3 is much lower than the first expansion rate of comparative examples 1-4.

[0088] Therefore, the present application can more evenly deposit silicon and lithium into porous carbon through a one-step "low-temperature deposition" method, and the carbon coating is more uniform and dense, so that the prepared negative electrode material has high capacity, high initial efficiency and high cycle performance, as well as low initial expansion rate.

[0089] 4: The button cell prepared from the porous silicon-carbon composite negative electrode material of Example 2 was subjected to charge and discharge tests. The results are as follows: Figure 2 shown.

[0090] from Figure 2 It can be seen that during discharge, the specific capacity achieved is 2024 mAh / g, during charge, the specific capacity achieved is 1927 mAh / g, and the first efficiency reaches 95.2%.

[0091] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved, and this document does not limit this.

[0092] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0093] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A method for preparing a porous silicon-carbon composite negative electrode material, characterized in that: include, Deposition of silicon and lithium: After the lithium salt and porous carbon are evenly mixed, they are placed in a PECVD device, the PECVD device is evacuated, the temperature is raised to a deposition temperature of 300-550°C, inert gas and silane gas are introduced into the PECVD device, and a radio frequency power supply power of 400-600W is used to deposit silicon and lithium on the porous carbon to obtain a negative electrode material precursor; wherein the specific surface area of ​​the porous carbon is 1000-2000m 2 / g; Carbon coating: The negative electrode material precursor is carbon coated to obtain a porous silicon-carbon composite negative electrode material.

2. The preparation method according to claim 1, characterized in that: The porous silicon-carbon composite negative electrode material comprises a core and an outer shell; the core comprises porous carbon and silicon and lithium deposited on the porous carbon, the core content is 97-98.2wt%, the outer shell is a carbon coating layer, the carbon coating layer content is 1.8-3.0wt%, wherein the lithium content in the core is 2-7wt%, and the silicon content is 40-50%.

3. The preparation method according to claim 1, characterized in that: The lithium salt is an inorganic lithium salt or an organic lithium salt; the inorganic lithium salt is one or more of lithium amide, lithium hydride, lithium hydroxide, and lithium carbonate; the organic lithium salt is one or more of methyl lithium, lithium acetate, lithium octanoate, lithium tetrahydroborate, lithium stearate, and lithium acetate; The average pore size of the porous carbon is 1.0 to 2.0 nm; The vacuum degree of the PECVD equipment is 1.0×10 -4 ~1.0×10 -1 Pa; The PECVD equipment is heated to 300-550° C. at a heating rate of 2-10° C. / min.

4. The preparation method according to claim 1, characterized in that: During the deposition of silicon and lithium, the flow ratio of the inert gas to the silane gas is 10:60 to 60:

60.

5. The preparation method according to claim 4, characterized in that: The inert gas is a mixture of one or more of nitrogen, argon and helium; The silane gas is a mixture of one or more of monosilane and disilane; When the silicon and lithium are deposited on the porous carbon, the reflected power of the PECVD device is 200-300W.

6. The preparation method according to any one of claims 1 to 5, characterized in that: During the carbon coating, an inert gas and a carbon source gas need to be introduced into the PECVD device; wherein the flow ratio of the inert gas to the carbon source gas is 10:60 to 60:

60.

7. The preparation method according to claim 6, characterized in that: The carbon source gas is a mixture of one or more of methane, acetylene, ethylene, and propylene; the inert gas is a mixture of one or more of nitrogen, argon, and helium.

8. A porous silicon-carbon composite negative electrode material, characterized in that: It is obtained by the preparation method described in any one of claims 1 to 7.

9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the porous silicon-carbon composite negative electrode material according to claim 8.

10. A lithium ion battery, characterized in that: It includes the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN117577819A

Cited By

  • Carbon source mixed gas CVD coated silicon carbon negative electrode material, preparation method and lithium ion battery

    CN120261549A